Centrality and transverse momentum dependence of inclusive J/ψ production at midrapidity in Pb–Pb collisions at sNN=5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akindinov, A.; et al. (Elsevier, 2020)
The inclusive J/ψ meson production in Pb–Pb collisions at a center-of-mass energy per nucleon–nucleon collision of √sNN = 5.02 TeV at midrapidity (|y| < 0.9) is reported by the ALICE Collaboration. The measurements are performed in the dielectron decay channel, as a function of event centrality and J/ψ transverse momentum pT, down to pT = 0. The J/ψ mean transverse momentum pT and rAA ratio, defined as p2 T PbPb/p2 T pp, are evaluated. Both observables show a centrality dependence decreasing towards central (head-on) collisions. The J/ψ nuclear modification factor RAA exhibits a strong pT dependence with a large suppression at high pT and an increase to unity for decreasing pT. When integrating over the measured momentum range pT < 10 GeV/c, the J/ψ RAA shows a weak centrality dependence. Each measurement is compared with results at lower center-of-mass energies and with ALICE measurements at forward rapidity, as well as to theory calculations. All reported features of the J/ψ production at low pT are consistent with a dominant contribution to the J/ψ yield originating from charm quark (re)combination
Keywords: J/ψ production; Pb–Pb collisions; Dielectron decay channel; Charm quark recombination; https://purl.org/pe-repo/ocde/ford#1.03.04